2003
DOI: 10.1086/502185
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Waterless Alcohol-Based Hand Rub in a Long-Term–Care Facility

Abstract: Objective:To examine the impact of introduction of an alcohol-based hand rub on hand hygiene knowledge and compliance and hand colonization of healthcare workers (HCWs) in a long-term-care facility (LTCF).Methods:Two floors of an LTCF participated. Ward A used the hand rub as an adjunct to soap and water; ward B was the control. HCWs' hands were cultured using the bag-broth technique forStaphylococcus aureus,gram-negative bacilli (GNB),Candida,and vancomycin-resistant enterococci (VRE). HCWs completed a questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
82
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 24 publications
0
82
0
1
Order By: Relevance
“…Infection rates decreased from 4.9 to 2.1 cases per 1,000 catheter days. The effectiveness of a self-study module combined with posters, fact sheets and lectures has since been further demonstrated in the ICU setting, with several studies showing significant decreases in catheter-related bloodstream infection (CRBSI) [17,[26][27][28], VAP [18,29] and hand hygiene adherence [30].…”
Section: Critical Care Healthcare Workersmentioning
confidence: 99%
“…Infection rates decreased from 4.9 to 2.1 cases per 1,000 catheter days. The effectiveness of a self-study module combined with posters, fact sheets and lectures has since been further demonstrated in the ICU setting, with several studies showing significant decreases in catheter-related bloodstream infection (CRBSI) [17,[26][27][28], VAP [18,29] and hand hygiene adherence [30].…”
Section: Critical Care Healthcare Workersmentioning
confidence: 99%
“…1 Two articles appearing in this issue of Infection Control and Hospital Epidemiology raise important issues pertaining to the position of alcohol hand rubs in the new guideline. 2,3 The first of these, by Dharan et al, describes a comparison of the antimicrobial efficacies of several waterless hand hygiene products when used at short application times (15 seconds). 2 These investigators compared one gel containing 60% ethanol with four alcohol-based rinses including a reference rinse containing 60% isopropyl alcohol in a crossover study of 12 volunteers in whom they tested the five hand rubs according to a modification of the European standard for establishing the efficacy of alcohol hand rubs (EN 1500).…”
mentioning
confidence: 99%
“…2 In the second of these, Mody et al attempt to measure the impact of an alcohol-based hand rub (62% ethanol gel) on compliance with hand hygiene in a long-term-care facility. 3 This was a four-phase interventional trial (ie, baseline, education, introduction of the alcohol rub, and longterm follow-up of the rub) conducted on two 36-bed wards of a long-term-care facility. On ward A, the rub was made available along with usual soap and water hand washing.…”
mentioning
confidence: 99%
See 2 more Smart Citations